2005
DOI: 10.1016/j.ccr.2005.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RalA is critical for Ras-induced tumorigenesis of human cells

Abstract: RalGEFs were recently shown to be critical for Ras-mediated transformed and tumorigenic growth of human cells. We now show that the oncogenic activity of these proteins is propagated by activation of one RalGEF substrate, RalA, but blunted by another closely related substrate, RalB, and that the oncogenic signaling requires binding of the RalBP1 and exocyst subunit effector proteins. Knockdown of RalA expression impeded, if not abolished, the ability of human cancer cells to form tumors. RalA was also commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
342
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(361 citation statements)
references
References 55 publications
19
342
0
Order By: Relevance
“…Studies demonstrated the importance of RalA and, more specifically, phosphorylation at S194 by AAK, in tumor development (6, 7, 10). The importance of RalA S194 phosphorylation in tumorigenesis makes AAK an attractive druggable target downstream of oncogenic Ras activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated the importance of RalA and, more specifically, phosphorylation at S194 by AAK, in tumor development (6, 7, 10). The importance of RalA S194 phosphorylation in tumorigenesis makes AAK an attractive druggable target downstream of oncogenic Ras activation.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi knockdown of endogenous RalA in PDAC cells significantly impaired anchorage-independent growth whereas knockdown of RalB impaired Matrigel invasion in vitro and experimental metastasis in vivo (6). Importantly, RalA-GTP and RalB-GTP levels were significantly higher in PDAC cell lines and in patient tumors relative to normal matched and unmatched samples (6, 7). Taken together, these studies suggest that therapeutic inhibition of Ral may be an effective therapy for KRAS mutant PDAC.…”
Section: Introductionmentioning
confidence: 93%
“…For example, in bladder and prostate cancer cells, RalB stimulates migration, whereas RalA is antimigratory (Oxford et al, 2005). In a defined model of Ras-driven tumorigenesis of human cells, RalA has been shown to promote transformation and tumor formation, while RalB has been shown to inhibit both (Lim et al, 2005). RalB depletion was also shown to trigger apoptosis in certain cancer cell lines, and this was reversed by simultaneous depletion of RalA and RalB (Chien and White, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on rodent tumorigenesis suggested that RalGEFs, and by extension RalA and RalB, are not particularly tumorigenic (White et al, 1995), recent results indicate more important roles for RalA and RalB in human cancer. For example, RalGEFs have been shown to be the most important effectors downstream of Ras in the transformation of human cells (Hamad et al, 2002) and RalA is a necessary component of Rasdriven tumorigenesis (Lim et al, 2005). Conversely, RalB has been shown to be pro-migratory in human bladder and prostate cancer cells (Oxford et al, 2005), and depletion of RalB via short interfering RNA (siRNA) has been shown to trigger apoptosis in many human cancer cell lines (Chien and White, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ral proteins (RalA and RalB) are members of the small GTPase Ras superfamily (Chardin and Tavitian, 1986) and play an essential role in a variety of physiological and pathological processes in mammalian cells, including exocytosis (Moskalenko et al, 2002;Cascone et al, 2008), cell proliferation (Chien and White, 2003;Lim et al, 2005), and oncogenic transformation (Rangarajan et al, 2004). As with other members of the Ras family, Ral cycles between its activated GTP-bound form and inactivated GDP-bound form in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%